Playing with the Social Network: Social Cohesion in Resettled and Non-Resettled Communities in Cambodia - Simone Gobien; Björn Vollan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Mutual aid among villagers in developing countries often is the sole possibility to insure against economic shocks. By using field laboratory experiments in Cambodian villages we study social cohesion in newly resettled and established communities which are both part of a land distribution project. All participants signed up voluntarily for the project, share comparable socio-demographic attributes and have similar preexisting network ties. We use a version of the solidarity game to identify the effect of a voluntary resettlement program on the willingness to help fellow villagers after an income shock. The voluntary resettled players only transfer between 41 % and 57 % of the amount the non-resettled players transfer to an anonymous community member. The solidarity differences are not only driven by lower expectations that the others would also help but are based on more selfish preferences among resettled farmers. Our findings are relevant for resettlement policies, because recipients might have to get additional compensation and formal insurance against the negative social consequences of resettlement until social cohesion is eventually re-established.
Keywords: C93; O15; O22; 330